Tissue-mimicking materials for elastography phantoms: A review. (November 2017) - Cao, Yanping; Li, Guo-Yang; Zhang, Xiao; Liu, Yan-Lin
Abstract: Ultrasound imaging can generate real-time images and is a low-cost, safe, and mobile imaging modality, which has broad applications in clinical radiology. During the past decade, ultrasound-based elastography has emerged as a highly useful technique for characterizing the mechanical properties of living soft tissues. Tissue-mimicking phantoms play an essential role in the development, validation, and use of elastography methods. Phantoms with desired acoustic and mechanical properties that are stable over time and can be stored in a broad range of temperatures have been pursued over the years. In this paper, we provide a brief overview of the typical phantom materials reported in the literature; in particular, we discuss the progress made in recent years and the open issues that deserve further investigation.